2021
DOI: 10.1002/admi.202101404
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Contact Mass Density and Thermal Conductivity Measurements of Organic Thin Films Using Frequency–Domain Thermoreflectance

Abstract: in thickness, [13,14] porosity, [15] polycrystallinity, [16] and growth morphology within these materials affect critical design parameters such as mass density (ρ) and thermal conductivity (κ). For example, mass density is a primary parameter in the detonation performance of explosive materials, as it is directly proportional to the resulting propagation velocity. [17,18] The thermal conductivity on the other hand, can provide key insights into the amorphous stability of pharmaceutical ingredients that ultima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Deposition conditions, film thicknesses, thermal conductivities, AlN (002) diffraction peak full-width at halfmaximum (FWHM) Values, and estimated grain size (GS) for the measured films deposited using various sputtering gas compositions increased contribution of the substrate to the probed thermal resistance. 35 The measured cross-plane thermal conductivities of our AlN films are displayed in Figure 2a and compared to values from the literature 18−20,29,34,36−41 as a function of deposition temperature. Red, green, and blue symbols mark films greater than 2 μm, 1−2 μm, and less than 1 μm in thickness, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deposition conditions, film thicknesses, thermal conductivities, AlN (002) diffraction peak full-width at halfmaximum (FWHM) Values, and estimated grain size (GS) for the measured films deposited using various sputtering gas compositions increased contribution of the substrate to the probed thermal resistance. 35 The measured cross-plane thermal conductivities of our AlN films are displayed in Figure 2a and compared to values from the literature 18−20,29,34,36−41 as a function of deposition temperature. Red, green, and blue symbols mark films greater than 2 μm, 1−2 μm, and less than 1 μm in thickness, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Section S7 of the Supporting Information, a global optimization sweeping the typical range of semiconductor–-dielectric interfaces was performed to extract the thermal boundary conductances and intrinsic conductivities that provided the best fit to our thermal model with the lowest uncertainty, examples of which are shown in Figure f. Films on c-Al 2 O 3 were analyzed in a similar manner but with slightly greater uncertainties in the thermal interfaces due to the increased contribution of the substrate to the probed thermal resistance …”
Section: Resultsmentioning
confidence: 99%
“…We use the measured cross‐plane thermal conductivities for the 65.8 and 133.0 nm films, deemed reasonable following an integrated sensitivity analysis (Section S11, Supporting Information). [ 51 ] The thermal resistance due to the Al/Ir and Ir/MgO interfaces is shown as the dotted black line for reference. A minimum in the effective cross‐plane thermal resistance is observed that is indicative of quasi‐ballistic c‐axis transport.…”
Section: Resultsmentioning
confidence: 99%